Biological Control of Sclerotium rolfsii, Causing Stem Rot of Groundnut by Pseudomonas cf. monteilii 9 - A.V. Manwar, Rakh R.R., L. S. Raut, S. M. Dalvi, and (Recent Research in Science and Technology, 2011)
In an attempt to develop effective biocontrol system for management of stem rot disease caused by Sclerotium rolfsii in groundnut, 11 Pseudomonas spp. isolated from rhizospheric soil, were evaluated for their antagonistic activity against Sclerotium rolfsii. A soil bacterium identified as, Pseudomonas cf. monteilii 9, showed highest antagonistic activity against Sclerotium rolfsii. In dual cultures, the Pseudomonas cf. monteilii 9 inhibited the Sclerotium rolfsii up to 94 % in terms of dry weight. Pseudomonas cf. monteilii 9 produced diffusible antibiotic, volatile metabolites, hydrogen cyanide and siderophore which affect Sclerotium rolfsii growth in vitro. This strain also produced a clear halo region on skim milk agar plates, indicating that it excretes protease which played vital role in inhibition of S. rolfsii. In pot assay for control of Sclerotium rolfsii, Pseudomonas cf. monteilii 9 treated seeds showed decrease in incidence of disease up to 45.45 to 66.67% in comparison to untreated seeds.